Oxford business law blog: oblb (University of Oxford, Faculty of law, 2016)
The Oxford Business Law Blog (OBLB) is a forum for the exchange of ideas and the reporting of new developments in all aspects of business law, broadly defined. Since its launch in March 2016, the OBLB has attracted readers from more than 150 countries.
Gesehen am 22.01.2019
Keywords: Weblog